IMPROVING MODELS FOR EFFICIENT RESOURCE ALLOCATION ON THE BASIS OF DIGITALIZATION IN INDUSTRIAL ENTERPRISES OF UZBEKISTAN (Web of Technology: Multidimensional Research Journal, 2025)
This article examines the issue of efficient resource allocation management in industrial enterprises of Uzbekistan under conditions of digital transformation. Based on the “Digital Uzbekistan – 2030” strategy and the regulatory and legal documents adopted on the digital economy, the importance of using digital technologies in enterprise activities is highlighted. In the research, resources are divided into labor, material, energy and financial groups, and their total volume is calculated according to the formula R = R_m + R_e + R_l + R_f. The efficiency of resource use is evaluated through the indicator E = Y / R. Using the example of two conditionally selected industrial enterprises, the indicators for the periods before and after digitalization are compared, and an increase in efficiency of up to 15–17 percent is observed. A simplified model based on linear programming is proposed for planning production volume under conditions of limited resources. The results of the study show the need to introduce digital monitoring of resources, to use ERP systems, and to expand data-driven management in industrial enterprises of Uzbekistan.